Molecular cloning and characterization of partial cDNA encoding for sucrose phosphate synthase from kelampayan (Neolamarckia cadamba) - Wong, Siew Chiao (University Malaysia Sarawak, UNIMAS., 2013)
Sucrose phosphate synthase (SPS) is a plant enzyme that has a crucial role in the biosynthesis of sucrose. Sucrose is critical for the maintenance of cellular metabolism, cell wall biosynthesis and respiration. Neolamarckia cadamba or locally known as Kelampayan is a light hardwood trees and source of raw materials for manufacturing of plywood, paper and short-fibred pulp. The aim of this study was to clone and characterize the cDNA encoding SPS gene from N. cadamba. Total RNA was isolated from leaf samples and reverse transcribed into cDNA by RT-PCR. The SPS gene was then amplified by PCR. The PCR product was purified and sent for automated sequencing. The sequence analysis of nucleotides and amino acids revealed the presence of a 598 bp partial cDNA sequence. The deduced amino acid sequence of SPS was homologous to the other known SPS proteins suggesting that it was derived from N. cadamba SPS gene. The SPS sequences from the study can serve as a foundation for further insight to understand the role of SPS protein and also for Kelampayan tree improvement purpose.